Motor imagery and action observation for predictive control in developmental coordination disorder - Steenbergen, Bert (Dev Med Child Neurol, 2020)
In 2019, international clinical practice recommendations on the definition, diagnosis, assessment, intervention, and psychosocial aspects of developmental coordination disorder (DCD) were published. Informing our understanding of mechanisms, recent systematic reviews have shown that children with DCD have difficulties with the predictive control of movements, including aspects of motor planning, which is expressed as the internal modeling deficit hypothesis. This motor control deficit is most evident when the spatial and temporal demands of a task increase. An increasing number of empirical studies suggest that motor planning problems can be remediated through training based on one or a combination of motor imagery and action observation. In this review, we show evidence of motor planning problems in children with DCD and show that task demands or complexity affects its appearance. Implications of these findings are treatments based on motor imagery and action observation to remediate motor planning issues. The article concludes with recommendations for future research.